L-band femtosecond fiber laser based on reduced graphene oxide polymer composite saturable absorber - Ng, E. K.; Lau, K. Y.; Lee, H. K.; Mohd Yusoff, N.; Sarmani, A. R.; Omar, M. F.; Mahdi, M. A. (Optica, 2021)
We demonstrate an L-band passively mode-locked erbium-doped fiber laser emitting at 1599.43 nm wavelength at a pulse train of 5.68 MHz. The microfiber reduced graphene oxide composite behaves as a saturable absorber that was fabricated using in-situ wet chemical and dip-coating methods. During operation, a single-pulse soliton was observed at a mode-locking threshold of 40 mW. This is a few times lower than most of the previous assessments in the same class of wavelength band and graphene saturable absorbers. The pulse duration was 568 fs with a maximum average output power of 6.75 mW. In addition, the superiority of this simple fabrication method facilitates its potential of mass production for applications in ultrafast photonics industries.